Chemical composition and in vitro digestibility of hay elefphantgrass cv. Paraíso - Gisele Machado Fernandes; Rosana Aparecida Possenti; Evaldo Ferrari Júnior; Valdinei Tadeu Paulino (Boletim de Indústria Animal, 2011)
We carried out a study to assess the dry matter related to exposure time for dehydration en shed, crude protein, mineral matter (ash), neutral and acid detergent fiber , hemicellulose and in vitro digestibility of elephantgrass cv Paraiso in three cutting ages. The experiment was installed in an area of 1.0 ha, already deployed with elephant grass Paradise in the Instituto de Zootecnia, Nova Odessa, São Paulo. The experimental design was a randomized block with three replications. The treatments were three cut (45, 60 and 75 days of growth). It was evaluated the level of dry matter elephangrass Paraiso, with samples collected at 0, 2, 4, 6, 24 and 30 hours of drying. Variables hemicellulose and neutral and acid detergent fiber increased with advancing age of the plant. There was a decrease in crude protein content and in vitro digestibility. The ages cutting had no effect on the ash level, dry matter increased with the age cut, showing a greater loss of water in the early hours of exposure for the deydration.